Accepting Financial Transactions Using Blockchain Technology and Cryptocurrency based on the TAM Model: A Case Study of Iranian Users - Masumeh Taheri Tolu; Narges Yazdanian; Hoda Hemmati; Hamidreza Kordlouoie (Iranian Journal of Accounting, Auditing & Finance)
This study aims to design a technology acceptance model (TAM) to accept financial transactions using blockchain technology and cryptocurrency transactions. By employing an unlimited sample of users by selecting 154 participants based on the Morgan table and analyzing the surveyed data with the Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicated that Perceived ease of use and Perceived usefulness positively and significantly impact the attitude toward cryptocurrency transactions supported by blockchain technology. Also, the attitude has a positive and significant impact on Iranian users' behavioral intention toward cryptocurrency transactions supported by blockchain technology. In addition, at a certain level of experience, users feel confident and can trust blockchain-based applications. Accordingly, governments, companies, and decision-makers should consider the results achieved in this study. The current study is the pioneer study in an emerging economy like Iran. The results may help policymakers mandate new regulations to new circumstances. This study mentions the influences of ease of use and usefulness of cryptocurrency transactions supported by blockchain technology.